2022
DOI: 10.1007/s00484-022-02302-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and physical activity: ambient temperature and urban trail use in Texas

Abstract: Individuals in the USA are insufficiently active, increasing their chronic disease risk. Extreme temperatures may reduce physical activity due to thermal discomfort. Cooler climate studies have suggested climate change may have a net positive effect on physical activity, yet research gaps remain for warmer climates and within-day physical activity patterns. We determined the association between ambient temperatures (contemporary and projected) and urban trail use in a humid subtropical climate. At a trail in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In another study in Austin, TX, researchers found pedestrians were more likely to use a hike and bike trail until 27 °C (81 °F) after which trail use decreased. 14 The different temperature values at which the regression slope changes between this study and ours may be related to differences in setting and type (ie, active transportation vs scheduled free play) of physical activity 41 impacting the behavioral threshold for heat.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In another study in Austin, TX, researchers found pedestrians were more likely to use a hike and bike trail until 27 °C (81 °F) after which trail use decreased. 14 The different temperature values at which the regression slope changes between this study and ours may be related to differences in setting and type (ie, active transportation vs scheduled free play) of physical activity 41 impacting the behavioral threshold for heat.…”
Section: Discussionmentioning
confidence: 63%
“…Physical activity and thermal comfort of children may be maximized by scheduling recess during cooler morning hours when researchers have found more pedestrians using a hike and bike trail in Austin, TX, on extreme heat days than other times. 14 In choosing when to schedule recess, schools should strike a balance between maximizing thermal comfort for physical activity promotion, providing a mental break from classroom instruction, and splitting up sedentary time during the school day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, studies that consider PA, SB and sleep duration at temperatures among different seasons are lacking. With continued greenhouse gas emissions and global warming due to urban development, we need to consider combining temperature management strategies with PA interventions to potentially promote comfortable and safe PA [ 35 ]. The freshmen are in a transitional phase from adolescence to adulthood, a critical time for developing healthy lifestyles and healthy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…PA intensity during recess may be modified by individuals' heat exposure and associated level of thermal comfort. With climate-related factors becoming increasingly recognized as drivers of PA [29][30][31], incorporating measures of heat exposure and shade during recess is particularly relevant in warm climates. For instance, in the humid subtropical climate of Austin, Texas, children were more likely to be observed under tree canopy during high ambient temperatures compared to lower temperatures, potentially seeking shade for thermal comfort [32].…”
mentioning
confidence: 99%